Mechanical metric for skeletal biomechanics derived from spectral analysis of stiffness matrix - Henyš, Petr; Kuchař, Michal; Hájek, Petr; Hammer, Niels (Scientific reports, 2021)
A new metric for the quantitative and qualitative evaluation of bone stiffness is introduced. It is based on the spectral decomposition of stiffness matrix computed with finite element method. The here proposed metric is defined as an amplitude rescaled eigenvalues of stiffness matrix. The metric contains unique information on the principal stiffness of bone and reflects both bone shape and material properties. The metric was compared with anthropometrical measures and was tested for sex sensitivity on pelvis bone. Further, the smallest stiffness of pelvis was computed under a certain loading condition and analyzed with respect to sex and direction. The metric complements anthropometrical measures and provides a unique information about the smallest bone stiffness independent from the loading configuration and can be easily computed by state-of-the-art subject specified finite element algorithms.
Keywords: biomechanika; algoritmy; Finite Element Analysis; Algorithms; Mechanical Phenomena; Biomechanical Phenomena; Bone and Bones; mužské pohlaví; teoretické modely; Biophysics; Models, Theoretical; mechanické jevy; spektrální analýza; kosti a kostní tkáň; ženské pohlaví; Humans; biofyzika; analýza metodou konečných prvků; Spectrum Analysis; Female; lidé; Male